PUTTING AN END TO THE TRAGEDY OF RANCHING IN NAPOLEON WRASSE FISHERY IN INDONESIA: A SOCIOLOGICAL APPROACH - Siti Arieta (Bajang Institute, 2022)
This study aims to look into Napoleon wrasse ranching in Anambas Islands Regency. Historically, the society in Anambas Islands has been socially constructed an unsustainable view of exploiting marine resources. In Napoleon wrasse fishery, overfishing has played a significant role in the loss of its populations. Due of the lack of adult Napoleon wrasse stock in marine ecosystem, larvae despite its high mortality rate are also sought as ranching target. It is found a tremendous amount of larvae are wasted in ranching period due low survival capacity to adapt to a caged ecosystem, so that the effectiveness of larvae ranching is questianable. Larvae fishing has become the object of the tragedy of the commons, whereas this particular activity plays an important role in the fishery. As a result, conservation and management have never been more important. The reflection to establish sustainable view is seen from discussion between Agent-Structure theory by Bourdieu and Agent-Network Theory by Latour. Local capacity to perform Locally Managed Marine Areas (LMMA) created major initiatives in delivering sustainable coral reef ecosystems which also form a natural environment of Napoleon wrasse